D-amino acid oxidase is expressed in the ventral tegmental area and modulates cortical dopamine. - Betts, J; Schweimer, J; Burnham, K; Burnet, P; Sharp, T; Harrison, P (Frontiers Research Foundation, 2014)
D-amino acid oxidase (DAO, DAAO) degrades the NMDA receptor co-agonist D-serine, modulating D-serine levels and thence NMDA receptor function. DAO inhibitors are under development as a therapy for schizophrenia, a disorder involving both NMDA receptor and dopaminergic dysfunction. However, a direct role for DAO in dopamine regulation has not been demonstrated. Here, we address this question in two ways. First, using in situ hybridization and immunohistochemistry, we show that DAO mRNA and immunoreactivity are present in the ventral tegmental area (VTA) of the rat, in tyrosine hydroxylase (TH)-positive and -negative neurons, and in glial fibrillary acidic protein (GFAP)-immunoreactive astrocytes. Second, we show that injection into the VTA of sodium benzoate, a DAO inhibitor, increases frontal cortex extracellular dopamine, as measured by in vivo microdialysis and high performance liquid chromatography. Combining sodium benzoate and D-serine did not enhance this effect, and injection of D-serine alone affected dopamine metabolites but not dopamine. These data show that DAO is expressed in the VTA, and suggest that it impacts on the mesocortical dopamine system. The mechanism by which the observed effects occur, and the implications of these findings for schizophrenia therapy, require further study.